2014
DOI: 10.1140/epjb/e2014-50064-x
|View full text |Cite
|
Sign up to set email alerts
|

The origins of multifractality in financial time series and the effect of extreme events

Abstract: Abst ract . T his paper present s t he result s of mult ifract al t est ing of two set s of financial dat a: daily dat a of t he Dow J ones Indust rial Average (DJ IA) index and minut ely dat a of t he Euro St oxx 50 index. W here mult ifract al scaling is found, t he spect rum of scaling exponent s is calculat ed via Mult ifract al Det rended F luct uat ion Analysis. In bot h cases, furt her invest igat ions reveal t hat t he t emporal correlat ions in t he dat a are a more significant source of t he mult ifr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…In [23] the authors studied again the Dow Jones Industrial Average taken on a daily basis plus the Dow Jones Euro Stoxx 50 sampled at one minute. In this case three analysis were performed:…”
Section: Source Of Multiscaling In Financial Data: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…In [23] the authors studied again the Dow Jones Industrial Average taken on a daily basis plus the Dow Jones Euro Stoxx 50 sampled at one minute. In this case three analysis were performed:…”
Section: Source Of Multiscaling In Financial Data: State Of the Artmentioning
confidence: 99%
“…The authors found that when shuffled, the dataset loses its multiscaling behaviour ( [23]). The shuffling of the intervals showed that the linearity of the scaling of the fluctuation functions worsen when the length of the interval is small and improves increasing it, thus according to the authors this should be regarded as a sign that the temporal correlations are the source of multiscaling.…”
mentioning
confidence: 99%
“…Financial time series present some key characteristics found in solar wind time series, namely chaoticity (Hołyst,Żebrowska & Urbanowicz 2001), multifractality, extreme events (Green, Hanan & Heffernan 2014) and turbulence (Voit 2005), which encourages the use of the same tools in the analysis of solar wind data. Loosely, the effects of current sheets and magnetic reconnections in the solar wind are qualitatively analogous to the effects of economic crises in financial time series.…”
Section: Introductionmentioning
confidence: 98%
“…In a previous paper [42], solving an ongoing debate in the literature (see, for example, Refs. [43][44][45]), it has been clarified that the true source of the multifractal behavior found in empirical financial time series is their causal structure. However, it was also shown that the measure of multifractality performed via the scaling of the moments in log-log scale is aggregation horizon dependent and that the true multifractal scaling should be measured in the limit of an infinite aggregation horizon.…”
Section: Introductionmentioning
confidence: 99%